Residues, spatial distribution and risk assessment of DDTs and HCHs in agricultural soil and crops from the Tibetan Plateau. (April 2016) - Wang, Chuanfei; Wang, Xiaoping; Gong, Ping; Yao, Tandong
Abstract: Due to its high elevation and cold temperature, the Tibetan Plateau (TP) is regarded as the "Third Pole". Different from other polar regions, which are truly remote, the TP has a small population and a few agricultural activities. In this study, agricultural soil and crop samples (including highland barley and rape) were collected in the main farmland of the TP to obtain the contamination levels of dichlorodiphenyltrichloroethane (DDT) and hexachlorocyclohexane (HCH) in the Tibetan agricultural system as well as the relevant human exposure risks. The average concentrations of DDTs and HCHs in the agricultural soil, highland barley and rape were 1.36, 0.661, 1.03 ng/g dw and 0.349, 0.0364, 0.0225 ng/g dw, respectively. In the agricultural soil, DDTs and HCHs matabolism (DDE, DDD and β-HCH) were abundant, which indicated a "historical" source, whereas crops contained a similar composition ((DDE + DDD)/DDT, α/β-HCH and α/γ-HCH) to that of wild plants, suggesting that the DDTs and HCHs in crops are likely from long range atmospheric transport. The human health risks via non-dietary and dietary to DDTs and HCHs in the farmland were assessed. All of the hazard index (HI) values of DDTs and HCHs for non-carcinogenic risks were <1, and most of the cancer risk values were <10 −6, suggesting that DDTs and HCHs in the farmland will not pose non-carcinogenic risks and will pose only very low cancer risks to the Tibetan residents. Highlights: Levels of OCPs in the Tibetan farmland were relatively low in a global perspective. OCPs in the Tibetan agricultural soil were from historical residues. OCPs in the crops mainly came from fresh input via atmospheric deposition. OCPs in Tibetan farmland will not pose non-cancer and cancer risks to the residents.